Rodent host specificity of european hantaviruses: Evidence of Puumala virus interspecific spillover - Klingström, Jonas; Heyman, Paul; Escutenaire, Sophie; Brus Sjölander, K.; De Jaegere, Florence; Henttonen, H.; Lundkvist, Åke (2002)
In order to investigate rodent host specificity of European hantaviruses, experimental infection of colonized and wild-trapped rodents was performed. In addition to the natural rodent reservoir, Clethrionomys glareolus, Puumala hantavirus (PUUV) could infect colonized Microtus agrestis and Lemmus sibiricus, but not Syrian hamsters or Balb/C mice. Neither C. glareolus, nor M. agrestis, could be readily infected by Tula hantavirus (TULV). Wild-trapped Apodemus flavicollis and A. agrarius, the natural reservoirs of Dobrava (DOBV) and Saaremaa (SAAV) hanta-viruses, respectively, could both be infected by SAAV. NMRI mice could also be infected by SAAV, but with lower efficiency as compared to Apodemus mice. Balb/C and NMRI laboratory mice, but not C. glareolus, could be infected by DOBV. To our knowledge, this is the first time DOBV and SAAV have been shown to infect adult laboratory mice. Moreover, potential hantavirus spillover infections were investigated in wild-trapped rodents. In addition to the natural host C. glareolus, we also found M. arvalis and A. sylvaticus with a history of PUUV infection. We did not find any C. glareolus or A. sylvaticus infected with TULV, a hantavirus which is known to circulate in the same geographical regions of Belgium. © 2002 Wiley-Liss, Inc. SCOPUS: ar.j FLWIN info:eu-repo/semantics/published